Plectrophenax nivalis (Fringillidae) - Füttern größerer Jungvögel im Nest - Georg Rüppell (IWF (Göttingen), 1969)
(de)Schneeammer. Betteln der Jungen, Futterübergabe, Bewegungen der Jungvögel im Nest (Putzen, Flügelrecken, Flugübungen), Wegtragen von Kotballen. The Snowbunting broods in caves in the Artic. Quite by accident, it was possible to film right into the nest. Shots with 64 f/s of feeding show details of food transfer and movements of the young in the nest.